Intact fibroblast growth factor 23 levels and outcome prediction in patients with acute heart failure - Anne Cornelissen (Nature Portfolio, 2021)
Abstract Elevated fibroblast growth factor 23 (FGF23) levels are associated with adverse outcome in populations with cardiovascular disease and chronic kidney failure. It is unclear if FGF23 has significance in prognosis estimation in patients with acute heart failure (HF) when compared to traditional risk estimation tools. Serum levels of intact FGF23 were assessed in 139 patients admitted to the Intermediate Care Unit of a tertiary hospital for acute HF. Patients were followed-up for one year. After exclusion of patients who were lost to follow-up, data outliers, and patients with sampling errors, the final study cohort comprised 133 patients. The Seattle Heart Failure (SHF) Model was used to estimate one-year survival. FGF23 levels correlated with HF severity and were strongly associated with one-year mortality. Associations between one-year outcome and FGF23, assessed on day 1 after admission, were still evident after multivariable adjustment (OR 15.07; 95%CI 1.75–129.79; p = 0.014). FGF23 levels predicted the one-year outcome with similar accuracy as the SHF Model, both if assessed on day 1 and on day 2 after admission (FGF23d1: AUC 0.784; 95%CI 0.669–0.899; FGF23d2: AUC 0.766; 95%CI 0.631–0.901; SHF: AUC 0.771; 95%CI 0.651–0.891). The assessment of FGF23 in patients with acute HF might help identify high-risk patients that are more prone to complications, need a closer follow-up and more aggressive treatment.